2006
DOI: 10.1038/nmat1733
|View full text |Cite
|
Sign up to set email alerts
|

Molecular computational elements encode large populations of small objects

Abstract: Since the introduction of molecular computation, experimental molecular computational elements have grown to encompass small-scale integration, arithmetic and games, among others. However, the need for a practical application has been pressing. Here we present molecular computational identification (MCID), a demonstration that molecular logic and computation can be applied to a widely relevant issue. Examples of populations that need encoding in the microscopic world are cells in diagnostics or beads in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…The group of de Silva reported the use of fluorescent tags, which are operated in binary and multivalued modes. [83] They decorated resin beads of Tentagel-S with a series of PET-active and -inactive anthracene derivatives, which mimic YES, NOT, PASS 0, and PASS 1 gates. The one-input operations were realized through pH changes and reading out of the characteristic blue anthracene fluorescence.…”
Section: Perspectives Beyond Computingmentioning
confidence: 99%
“…The group of de Silva reported the use of fluorescent tags, which are operated in binary and multivalued modes. [83] They decorated resin beads of Tentagel-S with a series of PET-active and -inactive anthracene derivatives, which mimic YES, NOT, PASS 0, and PASS 1 gates. The one-input operations were realized through pH changes and reading out of the characteristic blue anthracene fluorescence.…”
Section: Perspectives Beyond Computingmentioning
confidence: 99%
“…Moreover, a method based on molecular logic gates for tagging and identifying small objects in a large population has been proposed as a ready-to-use application for combinatorial chemistry. [27] It should be noted that computing devices based on (supra)molecular species and "soft" matter represent a radically different approach to information processing with respect to computers made from solid-state semiconductors. Therefore, comparisons between these types of systems should be made with care and, for certain aspects, may not make much sense.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…However, recent work showed that molecular logic devices could be interesting for specific applications in fields such as diagnostics, [10] medicine, [11] and materials science. [12] In fact, there are problems that not only can be solved by simple computations that are at hand for current molecular processors, but also need to be addressed in places where a silicon-based computer cannot go (e.g. inside a cell or in a membrane).…”
mentioning
confidence: 99%